Phenolic variations in mite infected leaves of Quercus ilex L. (Fagaceae) (PLANTA MEDICA, 2008)
Structures on the surfaces of leaves, such as dense layers of non-glandular trichomes, strongly affect phylloplane mite activities. On the other hand the feeding of eriophyoid mites on leaf surfaces can cause hyperplasia of leaf trichomes (erinea formation). In many cases the hyperplasia is accompanied by the accumulation of pigments within trichome cells, causing an impressive red-brown colouration of the eri- neum. There is no information, however, on the structure of these pigments as well as on the chemical alterations in the phenolic content of plant trichomes in response to mite attack. Erinea formation on the abaxial surface of Quercus ilex leaves upon Aceria ilicis (Acari: Eriophyoidea) attack provides an excel- lent model on this topic. Differences in the structure and chemical composition of isolated trichomes derived either from healthy (normal trichomes) or mite attacked (hypertrophic trichomes) leaves were examined. Carbon investment was comparable between the two different trichome types, but the cell walls of the hypertrophic trichomes appeared thinner and did not contain microcrystalline cellulose. Observations under the fluorescence microscope showed that the emitted fluorescence was different between the two trichome types, indicating a different composition in fluorescencing phenolic com- pounds. The chemical analyses confirmed that hypertrophic trichomes contained higher concentrations of the feeding deterrents proanthocyanidin B3 and catechin, as well as of quercetin-3-O-glucoside, but lower concentrations of acylated flavonoid glycosides, than the normal ones. The results showed that the structural and functional changes in leaf trichomes upon mite attack may be an effort of the leaf to compensate the damage caused by the pest

Polyphenol deposition in leaf hairs of Olea europaea (Oleaceae) and Quercus ilex (Fagaceae) (AMERICAN JOURNAL OF BOTANY, 1998)
The subcellular localization (cytoplasm, vacuoles, cell walls) of polyphenol compounds during the development of the multicellular nonglandular leaf hairs of Olea europaea (scales) and Quercus ilex (stellates), was investigated. Hairs of all developmental stages were treated with specific inducers of polyphenol fluorescence, and the bright yellow-green fluorescence of individual hairs was monitored with epifluorescence microscopy. During the early ontogenetic stages, bright fluorescence was emitted from the cytoplasm of the cells composing tie multicellular shield of the scales of O. europaea. Transmission electron micrographs of the same stages showed that these cells possessed poor vacuolation and thin cell walls. The nucleus of these cells may be protected against ultraviolet-B radiation damage. The progressive vacuolation that occurred during maturation was followed by a shifting of the bright green-yellow fluorescence from the perinuclear region and the cytoplasm to the cell walls. The same trends were observed during the development of the nonglandular stellate hairs of Quercus ilex, in which maturation was also accompanied by a considerable secondary thickening of the cell walls. Despite the differences in morphology, high concentrations of polyphenol compounds are initially located mainly in the cytoplasm of the developing nonglandular hairs, and their deposition on the cell walls rakes place during the secondary cell wall thickening. These structural changes during the development of the leaf hairs make them a very effective barrier against abiotic (UV-B radiation) and probably biotic (pathogenic) stresses.